2017
DOI: 10.1093/ofid/ofx163.452
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Strategies for Attenuating Changes in Bone Mineral Density in MSM on TDF/FTC HIV Pre-exposure Prophylaxis

Abstract: S220• OFID 2017:4 (Suppl 1) • Poster Abstracts safety of this practice in the real-world setting. The practice at our institution does not dose-adjust 3TC until CrCl is <30mL/minute; 100-150mg/d is prescribed for hemodialysis and CrCl 5-29mL/minute and 300mg/d for CrCl ≥30mL/minute.Methods. This cross-sectional study included HIV+ men and non-pregnant, non-lactating women aged ≥18 on higher-than-recommended 3TC doses as part of their antiretroviral regimen for ≥ 12 mo. A serum concentration (for Cmin) of 3TC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A DXA scan was generally read in a blinded fashion using a standardized protocol ( 29 ). A clinically significant change was defined as a decline of ≥3.0% for the lumbar spine and ≥4% for the femoral neck and total hip ( 27 ). Adverse effects associated with VD supplementation were also collected for the selected studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A DXA scan was generally read in a blinded fashion using a standardized protocol ( 29 ). A clinically significant change was defined as a decline of ≥3.0% for the lumbar spine and ≥4% for the femoral neck and total hip ( 27 ). Adverse effects associated with VD supplementation were also collected for the selected studies.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies did not find significant differences in changes of the hip and lumbar bone density among people living with HIV/AIDS (PLWHA) in both the VD and calcium supplementation group and the placebo group ( 26 ). Another study reported that there was no difference in the lumbar spine BMD in HIV-negative participants who participated in PrEP studies (−2.11 vs. −2.14%, p = 0.40) ( 27 ). The sample sizes were small and these studies were conducted in small regions, so that the generalizability of these findings was limited.…”
Section: Introductionmentioning
confidence: 99%